A meta-analysis of proactive personality and career success: The mediating effects of task performance and organizational citizenship behavior - Zhang, Zeyu; Fang, Han; Luan, Yuxiang; Chen, Qishu; Peng, Jianfeng (Frontiers in Psychology, 2022)
This study aims to reveal the impact of proactive personality on career success (i.e., subjective career success, salary, and promotion) and the sequential mediation effect of OCB and task performance on the relationship. Utilizing meta-analytic structural equation modeling (MASEM) technology including 101,131 employees, the results indicated slightly different findings of proactive personality and three types of career success. Specifically, in relation to salary, OCB and task performance independently transmit the effects of proactive personality to subjective career success, but they sequentially mediate this link as well. In regard to subjective career success and promotion, OCB (but not task performance) mediates the relationship between proactive personality and promotion. OCB and task performance sequentially mediate these links. We discussed findings cautiously and purpose future research directions.